Os significados de ocio/recreación nas constituições de países latino-americanos de língua espanhola - Alicia Maricel Oliveira Ramos (2012)
Despite the fact that this subject is largely acknowledged in internationaltreaties, few are the discussions pertaining to the right to leisure in LatinAmerica. Since it is cited in many Latin American constitutions, the issue of how this right is dealt with in each one was brought forth. Thinking about this reality gave rise to the following questions: What are the meanings that are attributed to leisure - and related terms, such as descanso, ocio, recreación, recreativo (a), tiempo libre and vacación(es), when one considers the Spanish language in constitutions of Latin American countries? With what approach, specificity and to what extent is this right discussed? When these subjects are considered in the context of such documents, which groups of people do they intend to takeinto consideration? In this exploratory study, a bibliographical and a documental research were conducted. The bibliographical research addressed the central themes of this dissertation (leisure, constitutions, social rights and Latin America). In addition, it served to gather facts about Latin America, which contributed to the better understanding of the conjunction in which the analyzed documents were inserted, and about social and historical questions of the context in which these documents were produced, with the goal to contextualize the research within the field in which it was intended. The documental research began with the selection of Latin American constitutions that: a) had some of thereference terms in its contents (leisure, descanso, ocio, recreación,recreativo(a), tiempo libre and vacación(es)); b) came into effect from 1990 onwards. A total of seven constitutions, from the following countries, were used: Colombia (1991), Paraguay (1992), Peru (1993), Venezuela (1999), Equator (2008), Bolivia (2009) and Dominican Republic (2010). The following step consisted on revealing, by content analysis, the meaning of leisure and related terms found in such constitutional texts. The reached results demonstrate that the recurring meanings attributed to leisure correspond to: 1) a compensating factor, related to work; 2) a part of character formation and development, related to education; 3) a differentiation from professional sport and manifestations ofsport that are connected to health, well-being and inclusion; 4) quality of life, of which leisure is considered a component, and when its also considered a fundamental right. Other meanings were also found. For instance, leisure may be an aid in social rehabilitation or part of a thought form that aims for development based on principals that are different from those of capitalism. The groups of people who benefit from leisure also became evident. The ones who stood out consisted of formal employees, children, adolescents and the elderly.